Extensions 1→N→G→Q→1 with N=M4(2) and Q=C3×S3

Direct product G=N×Q with N=M4(2) and Q=C3×S3

Semidirect products G=N:Q with N=M4(2) and Q=C3×S3
extensionφ:Q→Out NdρLabelID
M4(2)⋊1(C3×S3) = C3×C8⋊D6φ: C3×S3/C32C2 ⊆ Out M4(2)484M4(2):1(C3xS3)288,679
M4(2)⋊2(C3×S3) = C3×C8.D6φ: C3×S3/C32C2 ⊆ Out M4(2)484M4(2):2(C3xS3)288,680
M4(2)⋊3(C3×S3) = C3×C12.46D4φ: C3×S3/C32C2 ⊆ Out M4(2)484M4(2):3(C3xS3)288,257
M4(2)⋊4(C3×S3) = C3×D12⋊C4φ: C3×S3/C32C2 ⊆ Out M4(2)484M4(2):4(C3xS3)288,259
M4(2)⋊5(C3×S3) = C3×D12.C4φ: trivial image484M4(2):5(C3xS3)288,678

Non-split extensions G=N.Q with N=M4(2) and Q=C3×S3
extensionφ:Q→Out NdρLabelID
M4(2).1(C3×S3) = C3×C12.53D4φ: C3×S3/C32C2 ⊆ Out M4(2)484M4(2).1(C3xS3)288,256
M4(2).2(C3×S3) = C3×C12.47D4φ: C3×S3/C32C2 ⊆ Out M4(2)484M4(2).2(C3xS3)288,258